2022
DOI: 10.3390/ijerph19042218
|View full text |Cite
|
Sign up to set email alerts
|

Influence of “Face-to-Face Contact” and “Non-Face-to-Face Contact” on the Subsequent Decline in Self-Rated Health and Mental Health Status of Young, Middle-Aged, and Older Japanese Adults: A Two-Year Prospective Study

Abstract: This study aims to identify the independent influence of face-to-face contact (FFC) and non-face-to-face contact (NFFC) on the subsequent decline in self-rated health and mental health status by age. A total of 12,000 participants were randomly selected among residents in the study area, and 1751 of them responded to both the 2016 and 2018 mail surveys. The participants were subsequently classified into three age groups (25–49: Young adults; 50–64: Mid-aged adults; and 65–84: Older adults). Social contact was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…In another cross-sectional study, FFC had a moderating effect on loneliness and happiness, similar to non-FFC [14]. In a longitudinal study, FFC and non-FFC individuals had a lower risk of mental health decline than non-FFC individuals alone [15]. In another longitudinal study, FFC and/or non-FFC individuals with friends, neighbors, and workmates had a lower risk of new long-term care insurance certi cation than those who did not interact [16].…”
Section: Introductionmentioning
confidence: 82%
“…In another cross-sectional study, FFC had a moderating effect on loneliness and happiness, similar to non-FFC [14]. In a longitudinal study, FFC and non-FFC individuals had a lower risk of mental health decline than non-FFC individuals alone [15]. In another longitudinal study, FFC and/or non-FFC individuals with friends, neighbors, and workmates had a lower risk of new long-term care insurance certi cation than those who did not interact [16].…”
Section: Introductionmentioning
confidence: 82%
“…Interestingly, several studies indicated that the use of the internet undoubtedly lowered adverse life events and promoted social support (LaRose et al, 2001 ; Amichai-Hamburger and Ben-Artzi, 2003 ; Lewandowski et al, 2011 ). However, in improving mental health, face-to-face contact had a more significant effect as opposed to non-face-to-face contact (Achterhof et al, 2022 ; Fujiwara et al, 2022 ). In contrast, in improving social quality, interactions that took place online were better than face-to-face contact (Achterhof et al, 2022 ), which may be explained by Gonzales ( 2014 )'s findings that exhibit that text-based communication was more influential than face-to-face communication on self-esteem and further determined meaningful social interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The results show that self-perception of health and mood was worse during the period of strictest confinement than in the second survey, which coincided with less restrictive measures and more social contact ( 41 ). Several articles in the scientific literature report the beneficial effects of social support, contact and maintaining work for well-being, mood and health ( 40 , 42 , 43 ). During strict confinement, relationships mediated through ICTs increased, thus demonstrating their effectiveness as an alternative for social support ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%